Foto Hitam Putih Masyarakat Melayu Abad ke-19 Karya Gustav Richard Lambert: Black and White Photographs of the Malay Community of the 19th Century by Gustav Richard Lambert - Wan Lokman; Iwan Zahar; Arif Datoem (Wacana Seni Journal of Arts Discourse, 2018)
To add to the dearth of studies regarding photography in Malaysia, this essay focuses on the content analysis of six black and white images of the Malay community in the early 19th century that were taken by Gustav Richard Lambert in Malaya. Most of the photographs show the Malay cultures namely traditional custumes, music instruments and houses; some feature economic activities such as boat crafting while others portray the people of the Malay Sultanate from the common people to the high official and aristocrate family. Some of Lambert's photographs used full photo frames; some had compositions that were not common during that time such as a woman holding an umbrella but she does not look at the camera.